Study of Changing Mortality Patterns of Medico Legal Cases in relation to Covid Pandemic - Kumar , M U; Kumar , S K; Kiran , P P; Rao , P U M; Niha , C (Journal of Indian Academy of Forensic Medicine, 2023)
This century's most dreadful disease COVID-19 has created significant knock, effecting day to day life - economically, socially &  psychologically all over the world. This pandemic has affected not only thousands of people in terms of morbidity and mortality due to  spread of this disease, also made the medical world most affected. Nearly half of the world's 3.3 billion global workface had lost their  livelihoods in the pandemic period. Without the means to earn an income during lockdowns, many are unable to feed themselves and their  families. As bread winners lose jobs, fall ill and die, millions of dependents under the threat of livelihood and prosperity in all aspects. The  no. of road traffic accidents has decreased during 1st wave period and 2 wave period. There are varied patterns among all the sectors of  occupation with significant and surprising changes among private sector and business. The number of suicidal deaths shows an increase  st nd during the 1 wave period and decrease in 2 wave period.
Keywords: COVID-19; Mortality; Pandemic; 1 Wave; 2 Wave